Bioinoculants for the management of root-knot nematode, Meloidogyne incognita infecting banana - Narayana et al, R (Indian Journal of Plant Protection, 2018)
The most destructive and widely distributed nematodes affecting banana are Meloidogyne incognita, M. javanica, Rotylenchulus reniformis, Radopholus similis and Pratylenchus coffeae. Experiments were conducted in farmers’ felds at Dhanuvachapuram area of Trivandrum district of Kerala, for two consecutive years 2015-2016 and 2016- 2017 for the management of M. incognita, using biocontrol agents, viz., Pseudomonas ﬂuorescens and Trichoderma viride. P. ﬂuorescens sucker treatment + pit application (45 DAP) was the most effective treatment in increasing the yield of banana (27.2 t/ha) and reducing the population of nematodes in soil (166.7 nematodes/200 cc soil) and roots (63.8 nematodes/ 5g roots). This was followed by the application of P. ﬂuorescens sucker /rhizome treatment @ 5 g/sucker. P. ﬂuorescens sucker treatment + pit application (45 DAP) was statistically superior treatment in reducing the number of galls/5 g roots compared to control.